Emergency (Im)Mobilities. Insights from the Covid-19 Pandemic in Italy - Daconto, Luca; Caiello, Simone; Colleoni, Matteo (Fuori Luogo Journal of Sociology of Territory, Tourism, Technology, 2020)
The article presents an exploratory analysis of the (im)mobilities emerged during the pandemic of coronavirus disease 2019 (Covid-19) in Italy. The outbreak of Covid-19 and the resulting lockdown and social distancing measures have strongly affected urban societies on the move by precluding the movement for some ones and by generating a risky mobility for others or a movement without mobility. The authors focus on the role played by mobility regimes and the governance of emergency mobilities in influencing people’s motility and mobility. The aim is to point out the changes and inequalities caused by these emergency (im)mobilities and to gather insights that can be the basis for reflecting and planning about the urban mobility of the future. In the first section, the notions of mobilities, mobility regimes and emergency mobilities will be briefly reviewed in order to gather theoretical cues useful to orient the empirical exploration. In the second section, the main results of the empirical exploration will be presented. First, the attention is given to the changes in mobility behaviours during the pandemic. Then, the focus will be on the unevenness of (im)mobilities emerged during the pandemic period. Finally, on the basis of the results, the issue about the right to (im)mobility in the long-term and in diverse territories and cities will be discussed.